Pengembangan Prototipe Bahan Ajar Puisi Berbasis Multimedia 3D Flipbook (Prototype Development of 3D Multimedia-Based Poetry Teaching Materials Flipbook) - Yusra D (Jurusan Tadris Bahasa Indonesia, 2022)
This study aims to develop a prototype of poetry teaching materials based on 3D Flipbook multimedia. Through this research, it is hoped that there will be more varied teaching materials as well as learning media than the previous ones. The research design is a procedural descriptive research model, which is guided by the ADDIE model development research procedure initiated by Lee & Owens. Broadly speaking, this development model consists of 4 stages, namely: 1) analysis, 2) design, 3) development and implementation, and 4) evaluation. Thus, this research is a category of development research. The result of this research is poetry teaching materials in the form of 3D Flipbook multimedia. The results showed that according to 30 respondents, the 3D Flipbook multimedia display aspect was very feasible, the 3D Flipbook multimedia material aspect was feasible, and the 3D Flipbook multimedia learning aspect was very feasible. In conclusion, according to respondents, 3D multimedia flipbooks can be used as a very feasible alternative for learning poetry.Penelitian ini bertujuan mengembangkan prototipe bahan ajar Puisi berbasis multimedia 3D Flipbook. Melalui penelitian ini diharapkan tersedia bahan ajar sekaligus media pembelajaran yang lebih variatif dari yang sebelumnya. Penelitian pengembangan ini berpedoman pada model ADDIE yang terdiri atas empat tahap yaitu: 1) analisis, 2) desain, 3) pengembangan dan implementasi, dan 4) evaluasi. Hasil penelitian ini adalah bahan ajar puisi berupa multimedia 3D Flipbook. Â Berdasarkan respons dari informan dapat diketahui bahwa aspek tampilan dan pembelajaran multimedia 3D Flipbook sangat layak, serta aspek materi multimedia 3D Flipbook layak. Multimedia 3D Flipbook bisa dijadikan alternatif dalam pembelajaran puisi.